Near infrared light mediated photochemotherapy for efficiently treating deep orthotopic tumors guided by ultrasound imaging - Zuhua Wang; Shaoyan Xuan; Wenqi Qiu; Jiang Zhu; Xiaomeng Guo; Wei Li; Hanbo Zhang; Xiuliang Zhu; Yong-Zhong Du; Jian You (Taylor & Francis Group, 2017)
Recently, Combined cancer photothermal-chemotherapy has become a highly promising strategy in cancer treatment for its enhanced therapeutic efficacy, controlled drug release and reduced systemic toxicity. Almost all the reported strategies based on photothermal-chemotherapy have only focused on the treatment of superficial or subcutaneous cancer, which are not considered as a more clinically relevant and better predictive models of drug efficacy than orthotopic tumor models. Here, we reported an EphB4 receptor-targeting polymeric nanoplatform containing hollow gold nanospheres (HAuNS) and the anticancer drug paclitaxel (PTX) for cancer photothermal-chemotherapy. With the modification of the TNYL peptide, HP-TCS could specifically internalize into EphB4-positive SKOV3 and CT26 cells, further inducing the selective killing of the cells in co-cultured system, namely, EphB4-positive and EphB4-negative cells. Obvious targeting of the micelles into implanted orthotopic or subcutaneous tumors with high EphB4 expression was observed. Interestingly, increased accumulation of HP-TCS was observed in orthotopic colon tumors when compared with ectopic tumors. Highly specific accumulation of HP-TCS in EphB4-positive tumors significantly increased the feasibility of photothermal-chemotherapy mediated by the near infrared reflection (NIR) laser. Then, a systemic antitumor efficiency study was performed in implanted subcutaneous and visual orthotopic tumor models. Precise NIR laser irradiation could be localized on tumors under the guidance of B-mode ultrasound imaging, causing a rapid photothermal ablation effect limited to the region of tumors. Tumor growth was significantly inhibited by the photothermal-chemotherapy due to the triggered release of PTX. Our study provided a promising strategy of NIR laser-mediated photothermal-chemotherapy based on HP-TCS against the tumors (specially, deep orthotopic tumors) with high EphB4 expression.